ANALYSIS OF TEACHERS' PEDAGOGICAL COMPETENCE IN MUSIC LEARNING AT ELEMENTARY SCHOOL - Siswanti, Hilmi; Sularso, Sularso (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
This research addresses the challenge of limited knowledge and ability among classroom teachers in teaching music, especially in elementary schools without dedicated music teachers. The study aims to explore how class teachers implement their pedagogic competence in teaching music at Muhammadiyah Sokonandi Elementary School. Employing a qualitative approach, the research focuses on class II and class V teachers as the subjects. Data collection techniques encompassed observation to assess various aspects, including teachers' understanding of educational theories, practices, technology integration, teacher-student communication, and assessment methods. Additionally, interviews were conducted with grades II and V teachers, concentrating on nine indicators of teacher pedagogic competence in teaching music. These indicators encompassed understanding student characteristics, learning theories, curriculum development, and student potential. Complementing the data obtained from interviews and observations, documentation, such as descriptions of pedagogic competencies and photographs during research activities, was utilized. Data analysis involved data reduction, presentation, and drawing meaningful conclusions. The findings disclosed shortcomings in the application of the nine indicators of pedagogic competence in teaching music, specifically regarding the mastery of learning theory and facilitating student development. In conclusion, this research illuminates the challenges faced in music education at the elementary school level and contributes to enhancing the overall quality of music education. It underscores the significance of improving teacher pedagogic competence in music education to provide enriched learning experiences for students. The insights gained from this study can aid in the development of effective strategies for promoting music education in elementary schools.